The implications of macroenvironmental forces and SMEs investment behaviour in the energy sector: the role of supply chain resilience - Appiah, Michael Karikari; Sedegah, Daniella Delali; Akolaa, Rosemary Anderson (Heliyon, 2021)
Following a theory of strategic positioning perspective, this paper aims to explore the operating context in which dimensions of the macro-environment factors are likely to enhance Small and Medium Enterprise's (SMEs) intentions to invest in the Ghana's’ downstream oil and gas sector. Specifically, macro environment model has been developed wherein an important exogenous context (supply chain resilience) variable has been considered and studied its moderating effect on the relationship between macro environment dimensions and intentions to invest. The study also, examined the conditional effect of micro environment dimensions on intention to invest at different levels of supply chain resilience. Using Partial Least Square method we analyze cross sectional data across Ghana's SMEs spectrum between the periods 2017–2018. Our indicative evidence suggests that political factors, economic factors, environmental factors and technological factors are related to SMEs intentions to invest in the down stream oil and gas. Moreover, the research findings revealed that supply chain resilience moderated the relationship between macroenvironment dimensions and intention to invest. The link between macro environment dimensions and intention to invest was strengthened via the interaction effect of supply chain resilience. These robust results are consistent with the theory of strategic positioning. Overall, our results are akin to policy makers agenda to create enabling macro environment to improve local businesses participation in the Ghanaian oil and gas value chain. Besides, the findings will assist SMEs owners and managers in their decisi ons to invest in the downstream oil and gas sector by strengthening investment capability at different levels of Supply chain resilience.
Keywords: Downstream oil and gas; Ghana; Investment intention; Non-renewable energy PLS; Power; ACE: Energy and Environmental Sustainability; University of Energy & Natural Resources